Measuring therapeutic engagement in acute mental health inpatient environments: the perspectives of service users and mental health nurses - M. Chambers (BMC, 2021)
Abstract Background A key component of caring for service users (SUs) in acute mental health inpatient environments is Therapeutic Engagement (TE). To that end, the Therapeutic Engagement Questionnaire (TEQ) was developed and validated. The TEQ measures TE between SUs and registered mental health nurses (RMHNs) from the perspective of both parties and can quantify and recognise how nurses engage with SUs and monitor this activity as well as its enhancement of SU care and recovery. The aim of this study was to explore the views of SUs and RMHNs in relation to the TEQ and how it could be adopted into clinical practice within an acute inpatient environment. Methods As part of the validation stage of the development of the TEQ, the views of 628 SUs and 543 RMHNs were collected using a qualitative approach by way of free text at the end of the questionnaire. Two questions required free text response: – ‘what do you think of the TEQ?’, and ‘how can it be utilised?’ Results Following thematic analysis, it was found that both sets of participants stated that such a tool could be utilised to improve the service, could help nurses with reflective practice, be utilised as part of clinical supervision and to aid nurses’ professional development. The nurse participants also stated that such a tool would help track SU participation and enablement in their care. Furthermore, the nurses noted that the tool would help to reinforce the core ‘caring’ value of nursing and the overall goal of recovery. The SUs added that the TEQ would recognise the work of mental health nurses and provide them with a clear opportunity to express their views in relation to nursing staff. Conclusions Therapeutic engagement (TE) has been identified as part of the repertoire of mental health nursing and both groups of participants identified how a tool to assess this construct may be utilised in day-to-day clinical practice to the benefit of each group.